RETRACTED Exploring Teaching and Learning Physics in Engineering Institutions of Kathmandu Nepal - Ghimire, Pankaj Sharma; Luitel, Bal Chandra (LPPI Yayasan Almahmudi bin Dahlan, 2024)
Following a rigorous, carefully concerns and considered review of the article published in Educative: Jurnal Ilmiah Pendidikan to article entitled “Exploring Teaching and Learning Physics in Engineering Institutions of Kathmandu Nepal” Vol 2, No 1, pp. 11-23, 2024, DOI: https://doi.org/10.37985/educative.v2i1.263This paper has been found to be in violation of the Educative: Jurnal Ilmiah Pendidikan Publication principles and has been retracted.The article contained redundant material, the editor investigated and found that the paper published in KMC Journal to article entitled “Exploring Teaching and Learning Physics in Engineering Institutions of Kathmandu District” Vol 4, No 1, pp. 40-56, 2024, DOI: https://doi.org/10.3126/kmcj.v6i1.62327.The document and its content has been removed from Educative: Jurnal Ilmiah Pendidikan, and reasonable effort should be made to remove all references to this article.